Co-operating STAT5 and AKT signaling pathways in chronic myeloid leukemia and mastocytosis: possible new targets of therapy - Bibi, S.; Arslanhan, M. D.; Langenfeld, F.; Jeanningros, S.; Cerny-Reiterer, S.; Hadzijusufovic, E.; Tchertanov, L.; Moriggl, R.; Valent, P.; Arock, M. (Haematologica (Roma), 2014)
Chronic myeloid leukemia and systemic mastocytosis are myeloid neoplasms sharing a number of pathogenetic and clinical features. In both conditions, an aberrantly activated oncoprotein with tyrosine kinase activity, namely BCR-ABL1 in chronic myeloid leukemia, and mutant KIT, mostly KIT D816V, in systemic mastocytosis, is key to disease evolution. The appreciation of the role of such tyrosine kinases in these diseases has led to the development of improved therapies with tyrosine kinase-targeted inhibitors. However, most drugs, including new KIT D816V-blocking agents, have failed to achieve long-lasting remissions in advanced systemic mastocytosis, and there is a similar problem in chronic myeloid leukemia, where imatinib-resistant patients sometimes fail to achieve remission, even with second- or third-line BCR-ABL1 specific tyrosine kinase inhibitors. During disease progression, additional signaling pathways become activated in neoplastic cells, but most converge into major downstream networks. Among these, the AKT and STAT5 pathways appear most critical and may result in drug-resistant chronic myeloid leukemia and systemic mastocytosis. Inhibition of phosphorylation of these targets has proven their crucial role in disease-evolution in both malignancies. Together, these observations suggest that STAT5 and AKT are key drivers of oncogenesis in drug-resistant forms of the diseases, and that targeting STAT5 and AKT might be an interesting approach in these malignancies. The present article provides an overview of our current knowledge about the critical role of AKT and STAT5 in the pathophysiology of chronic myeloid leukemia and systemic mastocytosis and on their potential value as therapeutic targets in these neoplasms.